1998
DOI: 10.1080/1357332980030205
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Pedagogy and Teacher Change in an Urban High School: How Would You Like Tour Eggs Done?

Abstract: The use of culture is often applied to the change process. To address the problematic issues associated with using culture as a construct the metaphor of an egg is applied to individual change. This study examines the personal culture of an experienced male teacher of physical education and the change process he endured while implementing a sport education curriculum model to a class of grade nine students in an urban American high school. The teacher found that implementing a new pedagogy that challenged his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
1
19
0
2
Order By: Relevance
“…Professional culture is identified as the third theme influencing pre-service teachers' perception of TGfU. Professional culture refers to the personal culture that can affect change on an individual basis (Pope & O'Sullivan, 1998). In this study, most pre-service teachers reported that the traditional professional culture is dominant because few schoolteachers in Hong Kong apply the TGfU approach.…”
Section: Social Factors Influencing Pre-service Teachers' Perception mentioning
confidence: 98%
“…Professional culture is identified as the third theme influencing pre-service teachers' perception of TGfU. Professional culture refers to the personal culture that can affect change on an individual basis (Pope & O'Sullivan, 1998). In this study, most pre-service teachers reported that the traditional professional culture is dominant because few schoolteachers in Hong Kong apply the TGfU approach.…”
Section: Social Factors Influencing Pre-service Teachers' Perception mentioning
confidence: 98%
“…They identified five school norms that impacted a teacher's change process when implementing movement education and knowing these norms helped facilitate teacher change. Pope and O'Sullivan (1998) explored a teacher's professional culture as a new curriculum model, Sport Education, was introduced in physical education classes. The findings indicated that the school context influenced the teacher's willingness to make changes to the content and delivery of the program.…”
Section: Teacher Change Research In Physical Educationmentioning
confidence: 99%
“…However, the involvement of the principal in a physical education innovation has not always been a necessary component for change to occur (Cothran, 2001;Pope & O'Sullivan, 1998). Yet in studies where principals were involved in an innovation, they provided a positive impact, whereas a lack of principals' support tended to result in a negative impact on the change process (Faucette, 1987;Faucette & Graham, 1986).…”
Section: Enhancers To Changementioning
confidence: 99%
“…The other two issues including school culture and students' needs were reported in the two studies. The influence of school culture on a teacher's change process was the focus of the two studies conducted by Rovegno and Bandhauer (1997b) as well as Pope and O'Sullivan (1998), wherein five school norms were identified as having a positive impact on a teacher's change process in this study: a) the school philosophy; b) teacher learning; c)teacher participator power and responsibility; d) continual school improvement; and; e) the tendency "to feel that we can do anything" (p.407). Meanwhile, students' needs and new technology motivated teachers to seek professional development experience (Henninger, 2007;Pierre,1998;Sariscsany and Pettigrew, 1997 ;Pissanos and Allison, 1996;), especially new technology such as video and computer were shown to be more effective for teacher development than traditional instruments.…”
Section: In-service Teachersmentioning
confidence: 99%
“…In-service teachers Henninger (2007); Pissanos and Allison (1996); Bechtel and O'Sullivan (2007) ;Stroot, Collier, O'Sulliva and England (1994) Students behavior, beliefs and background, students' needs Henninger (2007); Pissanos and Allison (1996) District policy (negative) Bechtel and O'Sullivan (2007) School culture Rovegno and Bandhauer (1997b); Pope and O'Sullivan (1998) Statues of physical education (negative) Pissanos and Allison (1996); Bechtel and O'Sullivan (2007) Working place condition Doutis andWard (1999); Stroot et al (1994) Technology (computer science and video) Pierre (1998); Sariscsany and Pettigrew (1997) The assistance of clinical teachers Pre-service teachers Rikard and Knight (1997);Graber (1995) Culture and social difference Light and Tan (2006) …”
Section: Support From Principals Colleaguesmentioning
confidence: 99%